The effectiveness of using steel reinforce concrete in comparison with filexible bitumen with polymer modified binder and how it will affect the project time and cost : a case study at kuala lumpur international airport (KLIA) - Mohammad Haziq, Zamri (2013)
The structure of the runway must me good enough to make sure that the extreme pressure made by the aircraft when it is going to land, taxi, take-off, and the blast produce by the jet engine did not harm the runway. Steel reinforce concrete and flexible bitumen with polymer modified binder are among the materials that normally used in runway construction. Both of these materials have its own unique characteristics in term of effectiveness, maintenance record, and life span. Therefore, this study is aim to determine the effectiveness and life span of steel reinforce concrete and flexible bitumen with polymer modified binder in runway construction. The study was conducted at KLIA as it is the main airport in Malaysia and thousands of aircraft passes through the two main runways every year. KLIA uses flexible bitumen with polymer modified binder as the structure of the runway. The effectiveness and life span of the runway at KLIA are important in order to make sure that the operation at the airport become smooth and no interference will occur. Two engineers at the KLIA engineering department were the respondents that answering the close-ended questionnaire designed for this study. The questionnaire consists of certain elements on how steel reinforce concrete and flexible bitumen with polymer modified binder runway structure react on term of the materials behavior, maintenance frequency, cost and time consumes to build and maintaining the runway, and the life span of the runway. At the end of this study, the result concludes that the effectiveness and life span of both materials are bias towards the flexible bitumen with polymer modified binder rather that steel reinforce concrete because of its characteristics that is better and suit the runway construction and specification of KLIA. Hence, various types of runway structure materials and opinion from other engineer from different airport are recommended as it can evaluate more on the runway construction technology and may become beneficial for future reference in runway construction.